Characterization of the Consciousness Energy Healing Treated Cholecalciferol Using LC-MS and GC-MS Spectrometry - Dahryn Trivedi; Mahendra Kumar Trivedi; Alice Branton; Snehasis Jana (Journal of Advanced Pharmaceutical Science And Technology, 2021)
Vitamin D3 (cholecalciferol) is a fat-soluble vitamin, which widely used for the prevention and treatment rickets, osteoporosis, arthritis, Parkinson’s and Alzheimer’s diseases, autoimmune disease, dementia, glucose intolerance, etc. The impact of the Trivedi Effect®-Consciousness Energy Healing Treatment on the structural properties and the isotopic abundance ratio of cholecalciferol were evaluated using LC-MS and GC-MS spectroscopy. The test sample cholecalciferol was divided into control and treated parts. Only, the treated cholecalciferol was received the Trivedi Effect®-Consciousness Energy Healing Treatment remotely by a renowned Biofield Energy Healer, Dahryn Trivedi. The LC-MS spectra of both the samples at retention time (Rt) 22 minutes exhibited the mass of the molecular ion peak at m/z 385.25 (calcd for C27H45O+, 385.35). The LC-MS based isotopic abundance ratio of PM+1/PM in the treated cholecalciferol was increased by 0.74% compared with the control sample. But, the GC-MS based isotopic abundance ratio of PM+1/PM and PM+2/PM in the treated cholecalciferol was significantly increased by 66.39% and 62.69%, respectively compared with the control sample. Hence,13C, 2H, 17O, and 18O contributions from C27H44O+ to m/z 386 and 387 in the treated cholecalciferol were significantly increased compared with the control sample. The isotopic abundance ratios of PM+1/PM (2H/1H or 13C/12C or 17O/16O) and PM+2/PM (18O/16O) in the treated cholecalciferol were significantly increased as compared to the control sample. The increased isotopic composition of the Trivedi Effect®-Consciousness Energy Healing Treated cholecalciferol might have altered the neutron to proton ratio in the nucleus via the possible mediation of neutrino. The increased isotopic abundance ratio of the treated cholecalciferol may increase the intra-atomic bond strength, increase its stability. The new form of cholecalciferol would be better designing novel pharmaceutical formulations that might be more stable and more efficacious for the prevention and treatment of various diseases such as vitamin D deficiency, rickets, osteoporosis, arthritis, multiple sclerosis, cancer, diabetes mellitus, mental disorders, cardiovascular diseases, hypertension, infections, influenza, cognitive impairment in older adults, Parkinson’s and Alzheimer’s diseases, autoimmune disease, dementia, glucose intolerance, multiple sclerosis, etc.
Keywords: Cholecalciferol